Beyond Generation Z Stereotypes: Strategic Human Resource Alignment as an Organizational Mechanism for Building Work Ethic a Systematic Literature Review - Windayanti, Windayanti; Syah, Dewi Hani Kartini; Alfianti, Dian (Jurnal Ragam Pengabdian, 2026)
The growing dominance of Generation Z in the global workforce has prompted organizations to reassess the effectiveness of Strategic Human Resource Management (SHRM). Unlike previous studies that view Generation Z work ethic as an inherent generational characteristic, this study conceptualizes it as an outcome of an organization's ability to achieve Strategic Human Resource Alignment through strategic HR practices, psychological contracts, and person–organization fit. A Systematic Literature Review (SLR) following the PRISMA 2020 guidelines was conducted to synthesize evidence from peer-reviewed publications. The findings suggest that Generation Z work ethic is an organizationally shaped behavior fostered by fair, adaptive, transparent, and people-centered HR practices. These practices strengthen psychological contracts, enhance person–organization fit, and promote employee well-being, supporting long-term organizational sustainability. Based on these findings, this study proposes the Strategic Person–Organization Alignment Framework (SPOAF) as a conceptual model explaining how strategic alignment between organizations and employees shapes Generation Z work ethic.